KAWIN HAMIL PERSPEKTIF KOMPILASI HUKUM ISLAM DAN MAZHAB FIKIH - Mubaroq, Afif; Nelli, Jumni; M. April; zulikromi (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2025)
Marriage in Islam has clear regulations, as Allah SWT and His Messenger, Prophet Muhammad SAW, have established marriage as a form of worship to bring individuals closer to Him. Marriage serves several purposes, including fulfilling physical (biological) and spiritual needs, as well as forming a family, which is a means to continue and preserve a legitimate lineage. However, marriage as a means of fulfilling biological needs is often bypassed due to the prevalence of premarital sexual relationships, leading to pregnancy before marriage. The Kompilasi Hukum Islam (KHI), as the legal framework for Islamic law in Indonesia, regulates this matter in Article 53. Scholars hold diverse opinions regarding the legal status of pregnancy before marriage. This paper aims to further explore perspectives on pregnancy before marriage within the framework of Indonesian positive law and the views of Islamic scholars.